219 IMPROVING DELIRIUM SCREENING AND MANAGEMENT IN POST-ACUTE REHABILITATION: A MULTI-STAGE QUALITY IMPROVEMENT INITIATIVE. (18th November 2021) - McDaid, E; Harte, A; Reynolds, A; Hearne, S; Synnott, E; Buckley, E; Delaney, S; Cogan, L
Abstract: Background: There is risk of delirium among older patients on transition from acute care to post-acute rehabilitation (Marcantonio et al. 2003). The 4AT is the recommended delirium detection tool for clinical practice (Tieges et al. 2020). A multi-disciplinary led quality improvement project was undertaken to standardise and improve delirium screening and management in the older person's rehabilitation service of a post-acute rehabilitation hospital. Methods: A retrospective audit of medical charts was completed for all patients admitted to a post-acute older person's rehabilitation service from October 2019 to December 2019. Following that audit, there was a staff education intervention focusing on delirium awareness, screening and management. Furthermore, a dedicated 'Delirium Champions Group' was formed with representatives from the multi-disciplinary team. A Delirium Screen pro-forma was developed and implemented by this group. It included an attached 4AT sticker for all new admission medical charts. A post intervention medical chart audit was completed for all admissions to the same ward from October to December 2020. Results: The pre-intervention chart audit showed 0% compliance with any form of formal delirium screening tool. The majority of patients had at least 2 delirium risk factors at the time of admission. The post-intervention audit recorded 92% compliance with 4AT use at the time of admission as well as full completion of the Delirium Screen pro-forma which included the documentation of risk factors for delirium. The Delirium Champions Group provide ongoing staff education, resources and are now exploring hospital environmental design and its role in delirium prevention. Conclusion: This initiative lead to a significant improvement in the completion of delirium screening in post-acute rehabilitation. This project had the secondary benefit of prompting the formation of a dedicated delirium improvement group focusing on delirium awareness, screening, documentation, management and ultimately prevention.